Strategies and outcomes - Leitz, Lisa (Emerald Publishing Limited, 2024)
Fulfilling a need for innovative research that derives from multiple countries and time periods, Volume 48 of Research in Social Movements, Conflicts and Change offers a collection of cutting-edge scholarship on protest politics, effects of activism, and rights and equality based social movements. Split into separate parts on strategies and outcomes, chapters analyze the mobilization, organization, tactics, diffusion, repression, and successes/failures of social movements. Authors present research about attempts to make change on issues such as sustainability, animal rights, racial inequality, labor, white supremacy, and opposition to former U.S. President Donald Trump. In the same way that social movements influence policy and culture by raising awareness and framing issues, Strategies and Outcomes stands ready to influence future scholarship on these topics.
Keywords: Social movements -- United States -- 21st century.; Social conflict -- United States -- 21st cenutry.; Social Science -- Activism & Social Justice.; Political ideologies and movements.; Political activism -- Political engagement.; Social discrimination and social justice.; elektronické knihy; electronic books